2015
DOI: 10.4103/0301-4738.171965
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of posterior pole asymmetry analysis parameters of spectralis optical coherence tomography in detecting early unilateral glaucoma

Abstract: Purpose:To report the diagnostic ability of posterior pole asymmetry analysis (PPAA) parameters of spectralis optical coherence tomography (OCT) in detecting early unilateral glaucoma.Methods:A prospective, cross-sectional study which included 80 eyes of 80 normal subjects and 76 eyes of 76 patients with unilateral early primary open-angle glaucoma by Hodapp-Anderson-Parrish classification. All subjects were of age more than 18 years, best-corrected visual acuity 20/40 or better, and a refractive error within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“… 135 Posterior pole asymmetry analysis, although not presently having a built-in normative database, is highly reproducible and matches circumpapillary RNFL measurements in terms of diagnostic accuracy of early glaucoma. 136 , 138 Spectral-domain OCT may also be superior to SS-OCT in detecting GCIPL thinning in the outer temporal zone, 119 where the glaucomatous damage commonly occurs. 100 However, SD-OCT and SS-OCT have similar glaucoma diagnosis abilities based on macular inner layer thickness analysis.…”
Section: Diagnosis Of Glaucomamentioning
confidence: 99%
“… 135 Posterior pole asymmetry analysis, although not presently having a built-in normative database, is highly reproducible and matches circumpapillary RNFL measurements in terms of diagnostic accuracy of early glaucoma. 136 , 138 Spectral-domain OCT may also be superior to SS-OCT in detecting GCIPL thinning in the outer temporal zone, 119 where the glaucomatous damage commonly occurs. 100 However, SD-OCT and SS-OCT have similar glaucoma diagnosis abilities based on macular inner layer thickness analysis.…”
Section: Diagnosis Of Glaucomamentioning
confidence: 99%
“…By using the device employed in the present study (i.e., the Spectralis OCT), Rolle et al divided the posterior pole into 4 quadrants and identified the highest discriminating power in the inferior nasal quadrant (AUROC = 0.82) [10]. Dave et al also found the highest AUROC for the average inferior macular thickness (AUROC = 0.833) [19]. However, in these 2 studies, the 24-2 VF was used for central field sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…However, several studies comparing the diagnostic ability of the macular parameters to those of the traditional RNFL thickness with the different platforms showed contrasting results. 24 38 Specifically, studies using the Cirrus HD-OCT 26 30 and RTVue 31 34 instruments, comparing healthy subjects with patients with different stages of glaucoma, showed equivalent glaucoma diagnostic abilities of macular parameters (GCIPL or GCC, respectively) compared to peripapillary RNFL thickness (i.e., AUROC of the average GCIPL and GCC ranged from 0.735–0.964, and of average RNFL thickness from 0.735–0.972). 26 34 In other studies using RTVue OCT, average RNFL thickness performed better than the GCC in patients with preperimetric 35 and perimetric 36 glaucoma (i.e., AUROC of the average RNFL thickness ranged from 0.89035 to 0.91936 vs. 0.79035 to 0.86136 for GCC).…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 For all of these 3 commonly used SD-OCT platforms, a literature review generally suggests that the current commercially available SD-OCT macular software has the same or worse diagnostic potential as the traditional RNFL thickness parameter. 24 38 …”
mentioning
confidence: 99%
See 1 more Smart Citation